Pathway to mental health recovery: a qualitative and quantitative study on the needs of Chinese psychiatric inpatients. Issue 1 (December 2016) - Siu, B.; Tsang, M.; Lee, V.; Liu, A.; Tse, S.; Luk, H.; Lo, N.; Lo, P.; Leung, Y.
Abstract Background Exploration of the information and participation needs of psychiatric inpatients is an important step for the implementation of recovery-oriented mental health service. The objective of this study was to explore the information and participation needs of Chinese psychiatric inpatients in the largest psychiatric hospital in Hong Kong. Methods The study was divided into two parts. In the first part, eight focus groups with patients, patients' relatives and healthcare professionals were held to identify 22 items of information needs and 16 items of participation needs of Chinese psychiatric inpatients. Basing on the items identified in the first part of the study, a questionnaire was developed to survey on the importance of the different information and participation needs in the second part of the study. Participants were asked to rate in rank order their perceived importance of the items in the questionnaire survey. Results A hundred and eighty three Chinese psychiatric inpatients completed the questionnaire and the majority of them suffered from schizophrenia (68.3 %). For information needs, the top three needs rated by patients as the most important in descending order were: "Information on the classifications of mental illnesses, signs and symptoms and factors contributing to relapse", "Information on the criteria and arrangements for discharge", and "Information on the importance of psychiatric drug taking and its side effects". For participation needs, the top three needs rated by patients as the most important in descending order were: "Enquiring about personal needs and arrangements", "Keeping in touch with the outside world", and "Learning and practising self-management". Conclusions This study reveals that Chinese psychiatric inpatients are concerned about information on their mental illness and its treatments as well as the criteria for discharge. On the other hand, patients are concerned about their personal needs, their self-management, as well as their keeping in touch with the outside world during their hospitalisation. Moreover, patients with different socio-demographic and clinical characteristics have different information and participation needs. The results of the present study serve as a reference for designing guidelines, strategies, and programmes to meet the information needs and participation needs of psychiatric inpatients in Hong Kong.